PENDEKATAN FILOSOFI PENDIDIKAN TUT WURI HANDAYANI DALAM MENINGKATKAN KEMANDIRIAN BELAJAR DAN KARAKTER POSITIF SISWA KELAS 5 SEKOLAH DASAR - Imelda Meyvita; Jeslina Nogo Kabelen; Ahmad Ruslan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to explore the implementation of the educational philosophy "Tut Wuri Handayani" in enhancing learning independence and positive character among fifth-grade elementary students. This research employs a qualitative approach with a descriptive method, conducted in a public elementary school in East Jakarta during the 2024/2025 academic year. Data were collected through direct classroom observations and in-depth interviews with teachers and students. The findings reveal that applying this philosophy has a significant impact on students' initiative in the learning process. Observations indicate an increase in students' active participation in class discussions and activities, reflecting a drive for independent learning. Additionally, students show greater confidence and responsibility for their tasks, demonstrating positive values such as discipline, cooperation, and mutual respect in daily interactions. Teachers play a role as facilitators, creating an inclusive and supportive learning environment and implementing interactive learning methods, such as project-based learning and group discussions. Despite challenges in balancing encouragement with discipline, the results suggest that the "Tut Wuri Handayani" philosophy can foster positive character and enhance students' learning independence. This study recommends the consistent application of these philosophical principles to support the development of self-reliant and responsible students